Food label reading and understanding among obese adults: a population study in Malaysia. - , Rashidah Ambak; , Balkish Mahadir Naidu; , Mohd Azahadi Omar; , Nor Azian Mohd Zaki; , Syafinaz Mohd Sallehuddin; , Tahir Aris (Universiti Kebangsaan Malaysia, 2014)
Food labeling regulation has been implemented to enable consumers,including those with chronic diseases to make healthy informed choices before purchasing pre-packaged foods. The purpose of this study is to determine the prevalence of obese adults in Malaysia who practice reading food labels. It explored types of labels read and understanding of the information.Findings presented in this study were captured from the secondary analysis of National Health and Morbidity Survey’s (NHMS, 2006) food label study which focused only on obese adults (BMI > 30 kg/m2) aged 18 and above. This nation-wide cross sectional study was conducted from April to August 2006 using an interview-based questionnaire. Complex data analysis was done using Stata version 12.0.There were 4565 obese respondents with the mean age of 33 ± 9.7 (18 – 60 years old). About 54.7% completed high-school and 9.9% were higher degree holders. Prevalence of obese adults who claimed to read label was 80.5% (95%CI: 79.3, 81.6). Findings showed significant results in reading and understanding labels among all age group categories, Malay, Indian and other Bumiputras, all education categories and married respondents. Expiry date was the highest percentage being read (74.5%), followed by fat content (15.3%), vitamin (11.8%) and carbohydrate (10.9%).The obese population in Malaysia claimed to read and understand the food label but did not focus on specific macronutrients related to their health condition. Findings can be used to implement effective education programmes targeting the relevant groups to instill an awareness to read,understand and use the label information as one of the means in combating obesity.